1977
DOI: 10.1115/1.3443526
|View full text |Cite
|
Sign up to set email alerts
|

Erosive Effects of High Pressure and High Temperature Gases on Steel

Abstract: An experimental study is being conducted to determine the thermochemical mechanisms by which short duration pulses (1 to 2 ms) of high pressure and temperature gases erode steel. A ballistic compressor is used to generate the desired test gas conditions. The erosion of steel by oxygen-containing gases (e.g., air, O2/N2 mixtures) was found to be controlled by surface chemical reactions of oxygen. The erosion is linearly proportional to the oxygen mole fraction of the O2/N2 mixture. SEM examination of surfaces e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The erosion test was performed using a modified pressure-vented vessel designed by the authors [5,24,25]. The general structure of the device is shown in Figure 1.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The erosion test was performed using a modified pressure-vented vessel designed by the authors [5,24,25]. The general structure of the device is shown in Figure 1.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…The alloy undergoes a compositional transformation of carbides caused by the migration of Cr under thermal cycling conditions [20], and cracking due to the embrittlement of crystal grains at low temperature under the action of thermal stress during the thermal cycling between low-temperature and high-temperature regimes [21][22][23]. The hightemperature airflow erosion caused by propellant combustion is not a single erosion process, but a synergistic effect of various factors, including thermal shock, heat flow erosion on the surface of the material and possible chemical erosion [24], thus the erosion process and degradation mechanisms are also more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Moller (1973) has predicted that gas stream velocity in turbines at 750 C gives a threefold increase in rate of metal loss of Nimonic 80A (Ni-20Cr-5maxFe-2maxCo-2.5Ti-l.2Al-0.lmax C). Alkidas et al (1976Alkidas et al ( , 1977 have studied the E-C of AISI 4340 steel in pressurized gases (O-, H_, CO-, CO and N«) at 3000°K and found that material loss is greatest in oxygen containing gases.…”
Section: Effect Of Gas Flowmentioning
confidence: 99%